Effect of chitosan on causal agent of rice sheath blight disease, Rhizoctonia solani Kuhn - Saad, Nur Madhihah (2017)
Rice sheath blight disease is one of the destructive disease of paddy field that lowering the quality and yield of production. The causal agent is Rhizoctonia solani Kuhn. Chitosan has been used in agriculture as an alternative approach to chemical fungicides whereas in modern agriculture practices it is very important in managing the disease with minimum harm to the environment. In this study, chitosan had been used as antifungal to control the fungus R. solani. Chitosan at the rate of which were 2 and 4% caused 67.22 and 75.56% inhibition of mycelial growth, 58.45 and 91.96% inhibition of disease incidence and 76.10 and 99.00% inhibition of disease severity respectively. Chitosan acts as protection of rice stem from infection by R. solani. This study showed that chitosan has the potential to be introduced by the farmers in controlling the disease of rice sheath blight disease thus improving the plant quality via chitosan application.